Porodične karakteristike korisnika usluge smeštaja u ustanovi za vaspitanje dece i omladine - Urošević, Jovana; Žunić-Pavlović, Vesna (Specijalna edukacija i rehabilitacija, 2026)
Introduction. Family plays a crucial role in a child’s development. Different family circumstances, interactions, attitudes, and behaviors shape a child's life. Previous research suggests that the family environment of children who are in residential care within the social welfare system is characterized by a large number of risk factors and functioning problems. Objective. The objective of this research was to determine certain family characteristics of users placed in an institution for the education of children and youth. The paper examines the differences in family characteristics between those referred by the decision of the Social Services Agency and those on educational measure. Methods. The current research included users of the Institute for the Education of Children and Youth in Belgrade admitted in the period 2020–2024. The sample consisted of 55 children and youth aged 12–20 years, both boys and girls. The data was collected through the analysis of case records, using an instrument that was specifically constructed for this research. Results. Children and youth admitted to the educational institution come from families characterized by low socioeconomic status (50.9%), child maltreatment (61.8%), and pronounced problems of parents (67.3%). The two categories differ significantly in terms of the type of placement prior to admission to the institution and exposure to maltreatment in the family of origin. Conclusion. The results of the research suggest that treatment programs in educational institutions should focus more on interventions and support services for the families of children and youth admitted.
Keywords: family; residential care; child welfare system; educational measures